USING LITERATURE IN ENHANCING CONTENT AREA INSTRUCTION - Sama, Khadijat Muhammad (Sokoto Educational Review, 2020)
The relationship between English language and literature in English could not be overestimated. This paper takes a look at the relevance of literature in enhancing content area instruction and how best to reap the fruits of collaborative approach. A three point frame work via statement of the objectives, the activities to be employed towards attainment of the objectives and the assessment techniques are proposed. The paper however, contends that in order to enhance continued learning of the language beyond the four comers of the classroom, some obstacles or challenges must not only be checked but also be well addressed in that literature provides an avenue for language in use.